2013
DOI: 10.1007/s11748-013-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Shaggy and calcified aorta: surgical implications

Abstract: Atheroembolism is an emerging problem in cardiovascular surgery, especially in elderly patients. Severe atherosclerosis of the thoracic aorta usually reflects systemic atherosclerosis. Aggressive preoperative and intraoperative evaluation of the aorta using enhanced CT, transesophageal echocardiography and epiaortic ultrasound is important in elderly patients as well as those with systemic atherosclerosis. To prevent atheroembolism, it is important to select an adequate arterial perfusion site and to avoid tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 93 publications
1
36
0
4
Order By: Relevance
“…The exact definition of PA varied between authors, but the common denominator that best describes the clinical problem is aortic calcification that interferes with aortic cannulation, aortic clamping, aortotomy, or central coronary bypass anastomosis, necessitating modification of the surgical technique to avoid complications. 15 Diverse modalities are used for the diagnosis of PA, and there is a lack of clear definition for how PA should be diagnosed. Not uncommonly, PA is recognized by manual palpation performed after sternotomy and exposure of the aorta at the time of cardiac surgery.…”
Section: Definition and Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…The exact definition of PA varied between authors, but the common denominator that best describes the clinical problem is aortic calcification that interferes with aortic cannulation, aortic clamping, aortotomy, or central coronary bypass anastomosis, necessitating modification of the surgical technique to avoid complications. 15 Diverse modalities are used for the diagnosis of PA, and there is a lack of clear definition for how PA should be diagnosed. Not uncommonly, PA is recognized by manual palpation performed after sternotomy and exposure of the aorta at the time of cardiac surgery.…”
Section: Definition and Diagnosismentioning
confidence: 99%
“…The presence of a heavily calcified atheromatous aorta is associated with a significantly increased risk of embolic stroke and peripheral embolism during conventional cardiac surgery. 6,15,41 On the other hand, when calcification of the aorta is limited to the tunica media, it excludes a significant source of embolization because the intima is relatively intact without exophytic lesions but precludes safe cross-clamping or cannulation of the aorta. Nonetheless, the currently available diagnostic methods used to detect TAC, including CT, do not discriminate intimal from medial calcification, thus precluding a clear, clinically valuable separation between patients with PA.…”
Section: Nonatheromatous Aortic Disease: a Disease Of The Tunica Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Later, a technique for changing the blood temperature and the perfusion rate selectively in the upper and lower body depending on the purpose of the protected organs was also reported [8]. The ascending aorta and thoracic descending aorta are frequently selected as the cannulation route for perfusing the upper body, but this route is not appropriate in patients with profound atherosclerotic changes, such as a shaggy and calcified aorta [9]. Shiiya et al reported using antegrade perfusion by transapical aortic cannulation to prevent debris scattering due to retrograde perfusion from the femoral artery in a patient undergoing thoracoabdominal aortic repair by left thoracotomy [7], and Takemura et al reported the usefulness of transapical cannulation in preventing malperfusion during a deep hypothermic procedure to repair an acute traumatic descending aortic rupture [10].…”
Section: Discussionmentioning
confidence: 99%